Adapting mechanized vascular plant seed dispersal technologies to biocrust moss restoration. (19th July 2019) - Doherty, Kyle; Bowker, Matthew A.; Durham, Rebecca A.; Antoninka, Anita; Ramsey, Philip; Mummey, Daniel
Abstract : Biocrust restoration is an emerging field relevant to management of rangelands. Manual dispersal of biocrust is an effective approach, though there are few examples of biocrust restoration greater than a square meter, in part because specialized machinery has yet to be developed or adapted for dispersal across larger areas. Restoration with vascular plants is now conducted using a variety of equipment for work at small to large scales. We investigated the potential of two tractor draft implements, a rangeland seed drill and imprinter, to establish moss. We assessed three treatments: moss passed through a seed drill, manually broadcasted over imprinted soil, and manually broadcasted onto unaltered soil. We conducted these treatments at two sites that differed in management histories and vegetative cover. To use the seed drill to disperse moss we needed to amend moss materials to prevent jamming, which reduced application rate. Imprinted treatments established the most cover, a result we attribute to creation of favorable microsites for establishment. Broadcast methods established a comparable number of moss colonies to broadcast‐over‐imprinted soil, but less cover. Drill treatments were not effective by any metric, likely due to burial of moss. Final differences between our highest cover treatment and controls were positive, but small: 2.38% in imprinted versus 0.44% in controls. However, moss cover in imprinted areas increased during our two‐year experiment at this site, while controls did not. Future work should focus on integrating biocrust and vascular plant treatments and identifying equipment to efficiently achieve these goals.